2000
DOI: 10.1677/joe.0.1660677
|View full text |Cite
|
Sign up to set email alerts
|

Changes in actin network during calcium-induced exocytosis in permeabilized GH3 cells: calcium directly regulates F-actin disassembly

Abstract: Using digitonin-permeabilized GH3 cells, we investigated both the release of prolactin (PRL) and changes in the cytoskeleton. We determined that permeabilized GH3 cells released PRL in a dose-dependent manner upon addition of micromolar Ca 2+ . Phalloidin, a filamentous actin (F-actin) stabilizing agent, inhibited both Ca 2+ -dependent and -independent PRL release, whereas cytochalasin B, a destabilizing agent, had almost no effect on the release. Observation with a confocal laser scanning microscope revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…The amperometric results obtained with latrunculin A appear to be similar to those obtained with agents, such as ryanodine and caffeine that mobilise Ca 2+ from intracellular stores [5,14,17,36]. Thus, further experiments were carried out to study a possible relationship between Ca 2+ release from intracellular stores and the depolymerising effect of latrunculin in the absence of external Ca 2+ .…”
Section: Effect Of Ryanodine and Caffeine On Exocytosissupporting
confidence: 60%
See 1 more Smart Citation
“…The amperometric results obtained with latrunculin A appear to be similar to those obtained with agents, such as ryanodine and caffeine that mobilise Ca 2+ from intracellular stores [5,14,17,36]. Thus, further experiments were carried out to study a possible relationship between Ca 2+ release from intracellular stores and the depolymerising effect of latrunculin in the absence of external Ca 2+ .…”
Section: Effect Of Ryanodine and Caffeine On Exocytosissupporting
confidence: 60%
“…In fact, increases in the intracellular Ca 2+ concentration may induce F-actin depolymerisation [18,36]. It was also reported that increases in [Ca 2+ ]i mediated by high-affinity receptors for the Fc region of IgE (FcɛRI) in mast cells can be modulated by F-actin depolymerisation, which may thus affect Ca 2+ signalling [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…N-WASP is likely to be involved in the movement of secretory granules in GH4 cells because it was shown that prolactin secretion was dependent on the rearrangement of cortical actin (36 -38). This process would require remodeling of the cortical actin, which was both inhibitory to and required for secretion (37,38). The change from a stationary to a dynamic cytoskeleton could activate a kinase that then translocates to the nucleus to phosphorylate Elk1.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results and evidence from other reports, we propose the following potential mechanism whereby AQP4 regulates the migration of ANSCs. At the initial stage of cell migration, AQP4 might facilitate Ca 2+ influx (Faux and Parnavelas, 2007), which directly regulates actin depolymerization (Disanza et al, 2005;Yoneda et al, 2000). Ion influx increases cytoplasmic osmolality followed by water influx via AQP4 at the front end of the migrating cell .…”
Section: +mentioning
confidence: 99%